PRONOMINA BAHASA ONIN [Pronoun of Onin Language] - Siti Masitha Iribaram (TOTOBUANG, 2016)
One of local languages whose have  small number of native speaker in West Papua Province is Onin. This language is spoken by people who live in western and northwest of Bomberai Peninsula, Fak-fak Regency. Onin language, as well other languages in the world as, consists of few word classes. One of these is pronoun.  This paper used three stages of descriptive method. They were, collecting data stage, analyzing data stage and presenting the result of the data analysis.  Data, in this paper, was collected using interview method (metode cakap) through stimulation technique (teknik pancing) as a basic technique while face-to-face interview (cakap semuka) and noting technique (teknik catat) as advanced techniques. Thus, data analyzing used distributional method.  There are three types of pronoun in Ohin language,  personal pronoun, demonstrative pronoun, and questioner pronoun.  Salah satu bahasa daerah di Provinsi Papua Barat dengan jumlah penutur yang sedikit, yaitu bahasa Onin. Bahasa Onin dituturkan oleh masyarakat yang tinggal di Semenanjung Bomberai sebelah utara dan barat laut, Kabupaten Fakfak. Seperti halnya bahasa-bahasa lain di dunia, bahasa Onin terdiri atas beberapa kelas kata. Salah satu di antaranya adalah pronomina. Tulisan ini menggunakan metode deskriptif dengan tiga tahapan, yaitu tahap penyediaan data, tahap analisis data, dan tahap penyajian hasil analisis data. Penyediaan data tulisan ini menggunakan metode cakap dengan teknik pancing sebagai teknik dasar dan teknik cakap semuka serta teknik catat sebagai teknik lanjutan. Analisis data menggunakan metode distribusional. Ada tiga macam pronomina dalam bahasa Onin, yaitu (1) pronomina persona, (2) pronomina penunjuk, dan (3) pronomina penanya.